Illiberal Challenges To the European Union's Legitimacy From Within and Without: the Rule of Law and Refugee Crises - Saatcioğlu, Beken; Colella, Diğdem Soyaltın; Gülmez, Didem Buhari; Buhari Gülmez, Didem; Soyaltin Colella, Digdem (Taylor and Francis Group, 2022)
This study revisits the academic debate on rising populism and illiberalism in Europe that reduces the EU’s crises to those involving ‘liberal EU’ and ‘illiberal regimes’ without necessarily differentiating between these regimes. Applying Suchman’s multidimensional account of legitimacy to the EU, it unpacks the varying domestic contestations of two illiberal regimes against the different components of EU legitimacy within the context of two recent EU crises. Comparative analysis of how an illiberal insider (Hungary) and an illiberal outsider (Turkey) challenge the EU’s legitimacy in handling the rule of law and Syrian refugee crises, respectively, revealed two findings. First, Hungarian and Turkish actors raise divergent legitimacy contestations against the EU’s crisis management in the select cases. Second, their positionality towards the EU drives this divergence. While both countries seek to delegitimise the EU, their points of contention differ based on being in or outside the EU.
Keywords: Refugee; Legitimacy; Rule of law; European union; Illiberalism